Tight junctions in the blood–brain barrier promote edema formation and infarct size in stroke – Ambivalent effects of sealing proteins. Issue 1 (January 2021) - Winkler, Lars; Blasig, Rosel; Breitkreuz-Korff, Olga; Berndt, Philipp; Dithmer, Sophie; Helms, Hans C; Puchkov, Dmytro; Devraj, Kavi; Kaya, Mehmet; Qin, Zhihai; Liebner, Stefan; Wolburg, Hartwig; et al.
The outcome of stroke is greatly influenced by the state of the blood–brain barrier (BBB). The BBB endothelium is sealed paracellularly by tight junction (TJ) proteins, i.e., claudins (Cldns) and the redox regulator occludin. Functions of Cldn3 and occludin at the BBB are largely unknown, particularly after stroke. We address the effects of Cldn3 deficiency and stress factors on the BBB and its TJs. Cldn3 tightened the BBB for small molecules and ions, limited endothelial endocytosis, strengthened the TJ structure and controlled Cldn1 expression. After middle cerebral artery occlusion (MCAO) and 3-h reperfusion or hypoxia of isolated brain capillaries, Cldn1, Cldn3 and occludin were downregulated. In Cldn3 knockout mice (C3KO), the reduction in Cldn1 was even greater and TJ ultrastructure was impaired; 48 h after MCAO of wt mice, infarct volumes were enlarged and edema developed, but endothelial TJs were preserved. In contrast, junctional localization of Cldn5 and occludin, TJ density, swelling and infarction size were reduced in affected brain areas of C3KO. Taken together, Cldn3 and occludin protect TJs in stroke, and this keeps the BBB intact. However, functional Cldn3, Cldn3-regulated TJ proteins and occludin promote edema and infarction, which suggests that TJ modulation could improve the outcome of stroke.